2021
DOI: 10.3390/nu13093246
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Adherence and Nutritional Status in Dalmatian Kidney Transplant Recipients—Are They Related?

Abstract: The aim of this study was to evaluate adherence to Mediterranean diet (MeDi) and possible correlation of MeDi adherence and nutritional status parameters in Dalmatian kidney transplant recipients (KTRs). One hundred and sixteen KTRs were included in this study. Data about Mediterranean Diet Serving Score (MDSS), body mass composition, anthropometric parameters, clinical and laboratory parameters were collected for each study participant. The results showed 25% adherence to the MeDi in Dalmatian KTRs. MDSS show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Adherence to the MeDi among all study participants was an exceptionally low (8.9%), with an MDSS score of 8.32 ± 3.45, which is consistent with the results obtained on a healthy population from Kolčić et al [44], underlying poor adherence to the MeDi in southern Dalmatia. Furthermore, similar results were determined in our recent study conducted on kidney transplant recipients from the Dalmatia region, indicating poor adherence to the MeDi principles in this specific population [18].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Adherence to the MeDi among all study participants was an exceptionally low (8.9%), with an MDSS score of 8.32 ± 3.45, which is consistent with the results obtained on a healthy population from Kolčić et al [44], underlying poor adherence to the MeDi in southern Dalmatia. Furthermore, similar results were determined in our recent study conducted on kidney transplant recipients from the Dalmatia region, indicating poor adherence to the MeDi principles in this specific population [18].…”
Section: Discussionsupporting
confidence: 87%
“…Adherence to the MeDi, especially for those suffering from T2DM and CKD, has proven to be associated with reduction of cardiovascular risk, lower mortality risk, lower risk of CKD progression and lower levels of oxidative stress [ 10 ]. According to Gomes-Neto et al, greater adherence to the MeDi is associated with better kidney function outcomes in kidney transplant recipients (KTRs) [ 17 ], but low compliance to the MeDi principles was found in Dalmatian KTRs as demonstrated in our recent research [ 18 ].…”
Section: Introductionmentioning
confidence: 85%
“…More recently, a study involving 632 KT recipients followed-up for a median of 5.4 years showed that an increasing adherence to Mediterranean diet was associated with a lower risk of graft failure and kidney function decline, as well as graft loss [ 39 ]. Finally, adherence to Mediterranean diet was associated with better nutritional status (greater albumin levels and skeletal muscle mass) in Dalmatian KT recipients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted using the protocol described in our previously published study [25], where the methods have been described in detail.…”
Section: Methodsmentioning
confidence: 99%
“…A thorough examination of medical records, analysis of blood samples and 24 h urine samples was performed as previously described [25].…”
Section: Medical History and Clinical And Laboratory Parametersmentioning
confidence: 99%